P236 Endoscopic Recurrence or Anastomotic Wound Healing Phenomenon after Ileocolic Resection for Crohn's Disease: The Challenges of Accurate Endoscopic Scoring. (30th January 2023) - Van Der Does De Willebois, E; Duijvestein, M; Wasmann, K; D'Haens, G; van der Bilt, J; Mundt, M; Hompes, R; van der Vlugt, M; Buskens, C; Bemelman, W; ,
Abstract: Background: Adequate endoscopic scoring in Crohn's disease (CD) is crucial, as it dictates the need for initiating postoperative medical therapy and is utilised as outcome parameter in clinical trials. We aimed to observe anastomotic wound healing in relation to endoscopic scoring of both inverted and everted stapled lines in side-to-side anastomoses. Methods: Two prospective patient cohorts were included: ileocolic resection (ICR) for CD, and right-sided colon resection for colorectal cancer (CRC). Videos taken during colonoscopy six months postoperatively were evaluated. The SES-CD and modified Rutgeerts score were determined. Primary outcome was the presence of ulcerations in CD patients on both the inverted and everted stapled lines, fig1 . Secondary outcomes were the presence of anastomotic ulcerations in CRC patients and the number of cases having ulcerations exclusively at the inverted stapled line. Results: Of the 82 patients included in the CD cohort, ulcerations were present in 63/82 (76·8%) at the inverted- versus 1/71 (1·4%) at the everted stapled line. Likewise in the CRC cohort, ulcerations were present in 4/6 (67·7%) at the inverted versus 0/6 (0%) at the everted stapled line. 27% of the 63 patients in the CD cohort had ulcerations exclusively on the inverted stapled line. Conclusion: Inverted stapled lines heal with ulcerations, whereas the everted stapled line heal without any ulcerations, both in CD and non-CD patients. The abnormalities at the inverted stapled line might interfere with endoscopic scoring of recurrence, with potentially an impact on patients' quality of life and on health-care costs if postoperative treatment is initiated incorrectly.